2012
DOI: 10.1111/j.1440-1789.2012.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma of the sellar region mimicking pituitary adenoma

Abstract: We report here the case of an 82-year-old woman who presented with visual disturbance. MRI demonstrated a sellar mass. The diagnosis of pituitary adenoma was made. She underwent transnasal surgery. Histologic, immunohistochemical and ultrastructural studies indicated that the tumor was a melanoma. Despite an exhaustive search for a primary lesion elsewhere, none was found. The sellar tumor was considered a primary lesion, although extrasellar primary tumor imaging cannot be excluded with 100% certainty. Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Many melanocytes can be found around the floor of the sella, predominately in the meningeal lining, the ventrolateral regions of the medulla oblongata, and around the spinal cord [9,15,17]. Metastatic melanomas represent spread from a primary tumor developing in the skin, or less commonly the lungs, gastrointestinal tract, retina, or other distant sites [4,6,18,19]. Metastatic melanoma usually grows rapidly and has a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many melanocytes can be found around the floor of the sella, predominately in the meningeal lining, the ventrolateral regions of the medulla oblongata, and around the spinal cord [9,15,17]. Metastatic melanomas represent spread from a primary tumor developing in the skin, or less commonly the lungs, gastrointestinal tract, retina, or other distant sites [4,6,18,19]. Metastatic melanoma usually grows rapidly and has a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of previous reported cases of primary melanocytic tumors of the sella, few reports presented MIB-1/Ki-67 indices. A high MIB-1/Ki-67 index was associated with a more progressive symptomatic course [6,9]. Rousseau et al [15] reported a MIB-1/Ki-67 index of 3% with a 4 year clinical history.…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations